The Structure of Wartime Strategic Communications: Case Study of the Telegram Channel Insider Ukraine - Karpchuk, Nataliia; Yuskiv, Bohdan; Pelekh, Oksana (Politologija, 2022)
This article focuses at the issue of strategic communications of Ukraine during the Russian-Ukrainian war, which began on February 24, 2022. The authors consider strategic communications as a system consisting of invariant and variable components that can be projected in media reports. The authors proceed from the fact that, on the one hand, the media are an instrument of strategic communications, and on the other, strategic communications are transformed, reflected in media reports. The study is aimed to reveal the structure of strategic communications, which is characteristic of the period of armed conflict. Reports of the Insider Ukraine Telegram channel during the first 100 days of the war were analyzed. On the basis of a reflexive thematic analysis, using a one-way dispersion analysis, it has been found out that the strategic communications of Ukraine during the war period consist of the following invariant components: interactive communications of Ukraine, operational communications of Ukraine, extraoperational communications of Ukraine, operational and extraoperational communications concerning the RF. These generalized components have their own sub-components, the intensity or total absence of which in media reports can be related to specific events of the war period. This study contributes to the understanding of the structure of strategic communications in general and during the war in particular.